Removal of Lithium Ions from Aqueous Solutions by an Ultrafiltration Membrane Coupled to Soluble Functional Polymer - Sanchez-Poblete, J; Roa-Ruiz, K; Oyarce-Riveros, E; Salazar-Marconi, P; Boulett-Neira, A; Boulett-Neira, A (Elsevier B.V., 2022)
In this research, the separation and concentration of lithium ions (Li+) from the aqueous solution was studied by the liquid-phase polymer-based retention technique (LPR) using poly(sodium styrene sulfonate) (PSSNa), poly(potassium sulfopropylacrylate) (PSPAK) and poly(sodium acrylate) (PAS). These polymers were characterized by Fourier transform spectroscopy and thermogravimetric analysis, corroborating their correct formation. In addition, the ability to remove Li+ from water was studied, as a function of the amount of polymer, the pH of the solution and the initial concentration of Li+. The study of isotherms and the removal of Li+ in the presence of interferents was also carried out. Finally, the reuse of the polymer was evaluated in consecutive adsorption–desorption cycles. Based on the obtained results, it was determined that a polymer: metal molar ratio of 20: 1 at pH 5.7, was the most suitable for use in the LPR process. A Li+ removal efficiency (% R) of more than 80% was obtained. Among the polymers studied, PSPAK is the water-soluble polymer with the highest % R of Li+ and it achieves adequate permeation flux during LPR experiments (43.2 L h-1m−2). The experimental data obtained from the removal of Li+ were better adjusted to the Freundlich isothermal model. On the other hand, using 1:20Li+:interfering ion molar ratio, the Li+ removal efficiency of the LPR process decreases to 40% for Na+ or K+ and decreased to 20% for Mg2+ interfering ions. The polymer can be reused up to the fourth consecutive cycle, reaching a removal efficiency of 46%. © 2022 Elsevier B.V.